The World of Values of Polish and Hungarian Students – A Comparative Study - Cekiera, Rafał (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2024)
This article presents the results of a comparative study on the world of values of Polish and Hungarian university students. During the research queries, a tool allowed both the respondents’ axiological self-identification and the expression of opinions on socially emotive issues. The research project made it possible to identify both similarities and interesting differences in the value systems of the students of the two countries analysed. Hungarian students were less likely to declare themselves as believers and to give less importance to religion, while at the same time being much more likely than Polish students to consider that the Christian value system should be the basic foundation for Europe. Another interesting point may be the identified difference between the different dimensions of the world of values of men and women. In both Poland and Hungary, female students are more worldly liberal, while male students are conservative and refer more often to tradition.